2. KERJASAMA INDONESIA â€“ BRASIL DALAM PENANGANAN PERDAGANGAN NARKOTIKA ASAL BRASIL DI INDONESIA PERIODE 2010-2015 - Abihail, Didier; Susiatiningsih, Hermini; Hanura, Marten (Journal of International Relations, 2017)
Indonesia is a big a country that being targeted by international narcotics trafficker which is Transnational Organized Crime. One of the example is the Brazilian who tried to smuggle narcotics to Indonesia. This research is using two cases of studies, i.e. Rodrigo Gularte that has been apprehended in 2003 and Reginaldo Bom Fim is in 2012 by Indonesian National Police for smuggling Brazilian narcotics to Indonesia. In this regard, Indonesia â€“ Brazil cooperation on combating narcotics becomes an interesting point to be studied. The research questions of this study is â€œHow is Indonesia â€“ Brazil cooperation on combating narcotics originated from Brazil? ; and Is there any factors that might supports or detains the cooperation?â€ The point of this research is to explain the procedure of cooperation between Indonesia â€“ Brazil on combating drugs and explaining the factors that tied this cooperation. This research is using Liberalism theory and Implementation Policy theory. The Liberalism is being used to explain the procedure of cooperation between two countries effectively and then being ratified to be implemented. Also Implementation Policy theory is used for explaining the procedure of implementation on combating the drugs. Descriptive methods are being used in this research to explain the cooperation and the implementation of combating drugs policy. As the result, this study found that Indonesian â€“ Brazil cooperation formally established after legal basis has been ratified, and then implemented by two ways of cooperation, which are cooperation between the Government (G to G) and cooperation between national police department (P to P). As for the process of cooperation, has its own tidal wave caused by inhibitor and stimulant factors by the two cases thatâ€™ve been the fundamental to this research. The stimulant factors that being referred is the two cases indicate that both of the party needs to cooperate to combat against TOC; both party shared common aspiration and commitment on combating against TOC. The inhibitor factors that being referred is about death penalty still being used towards narcotics convict and difficulties to gather inteligence source for combating narcotics trafficking.